A secure routing protocol with trust and energy awareness for wireless sensor network - Ahmed, A. (Springer New York LLC, 2016)
Nodes in most of the deployments of Wireless Sensor Networks (WSNs) remain un-administered and exposed to variety of security attacks. Characterized by constrained resources and dynamically changing behavior of sensor nodes, reliable data delivery in WSNs is nontrivial. To counter node misbehavior attacks, traditional cryptographic and authentication based solutions have proved to be inappropriate due to high cost and incapability factors. Recently, trust based solutions have appeared to be viable solutions to address nodes’ misbehavior attacks. However, the existing trust based solutions incur high cost in trust estimation and network-wide dissemination which significantly increases traffic congestion and undermines network lifetime. This paper presents a Trust and Energy aware Secure Routing Protocol (TESRP) for WSN that exploits a distributed trust model for discovering and isolating misbehaving nodes. TESRP employs a multi-facet routing strategy that takes into consideration the trust level, residual energy, and hop-counts of neighboring nodes while making routing decisions. This strategy not only ensures data dissemination via trusted nodes but also balances out energy consumption among trusted nodes while traversing through shorter paths. Demonstrated by simulation results in NS-2, TESRP achieves improved performance in terms of energy consumption, throughput and network lifetime as compared to existing solutions.